Analysis of the Mechanism of Action of the Antisense RNA That Controls the Replication of the repABC Plasmid p42d - Cervantes-Rivera, Ramón (American Society for Microbiology (ASM), 2010)
Replication and segregation of the Rhizobium etli symbiotic plasmid (pRetCFN42d) depend on the presence of a repABC operon, which carries all the plasmid-encoded elements required for these functions. All repABC operons share three protein-encoding genes (repA, repB, and repC), an antisense RNA (ctRNA) coding gene, and at least one centromere-like region (parS). The products of repA and repB, in conjunction with the parS region, make up the segregation system, and they negatively regulate operon transcription. The last gene of the operon, repC, encodes the initiator protein. The ctRNA is a negative posttranscriptional regulator of repC. In this work, we analyzed the secondary structures of the ctRNA and its target and mapped the motifs involved in the complex formed between them. Essential residues for the effective interaction localize at the unpaired 5′ end of the antisense molecule and the loop of the target mRNA. In light of our results, we propose a model explaining the mechanism of action of this ctRNA in the regulation of plasmid replication in R. etli.